2000
DOI: 10.1089/acm.2000.6.235
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of C-Reactive Protein Levels and Body Temperature of an Elderly Patient Infected withPseudomonas aeruginosaon Treatment with Mao-Bushi-Saishin-To

Abstract: In cases in which the fever does not fall in response to antibiotics for at least 3 days, half of the standard dose of Mao-bushi-saishin-to for 7 days might be worth trying to induce remission, especially for elder patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In addition, Ephedrae is less reported on antidepressants. From the clinical application of MFX, MFX is widely used in respiratory and immune system diseases due to strong anti-inflammation and antianaphylaxis [35, 39, 65, 66]. Nevertheless, the impact on antidepressant is limited.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Ephedrae is less reported on antidepressants. From the clinical application of MFX, MFX is widely used in respiratory and immune system diseases due to strong anti-inflammation and antianaphylaxis [35, 39, 65, 66]. Nevertheless, the impact on antidepressant is limited.…”
Section: Discussionmentioning
confidence: 99%
“…A. radix is primarily derived from either Asiasarum heterotropoides or Asiasarum sieboldii (6). Studies has been performed regarding the anti-inflammatory and anti-allergy effects of A. radix (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous studies using mice showed that the administration of MBST increases the production of the titer of antibodies against influenza, especially in older mice [ 15 , 16 ]. On the other hand, Kamei et al (2000) reported a case study showing that MBST remitted inflammatory markers and fever; in brief, fever and C-reactive protein levels returned to normal in an elderly patient even though antibiotics did not improve the outcome [ 17 ]. Results of these clinical studies and some preclinical evidence [ 18 , 19 , 20 , 21 ] indicate that MBST may be effective against upper respiratory tract infection because of its anti-inflammatory effect and adjuvanticity.…”
Section: Introductionmentioning
confidence: 99%